The Impact of Cardiovascular Disease and Risk Factor Treatment on Ethnic Disparities in Kidney Transplant. (May 2013) - Taber, David J.; Pilch, Nicole A.; Meadows, Holly B.; McGillicuddy, John W.; Bratton, Charles F.; Chavin, Kenneth D.; Baliga, Prabhakar K.; Egede, Leonard E.
There is limited data on the use of cardiovascular disease (CVD) risk factor medications following renal transplant, especially when comparing use across ethnicities. The aim of this study was to compare the incidence, treatment, and impact of CVD between ethnicities in kidney transplant recipients. This was a retrospective cohort study of adults who underwent transplant between 2000 and 2008 within our academic medical transplant center. Pediatrics, multiorgan transplants, and those lost to follow-up were excluded. Data collection included all transplant and sociodemographic characteristics, medication use, CVD risk factor management, and follow-up events, including acute rejection, graft loss, and death. A total of 987 patients were included and followed for a mean of 6.7 ± 3.0 years. The baseline demographics revealed black patients were equally likely to have preexisting CVD (24% vs 25%, P = .651), but more likely to have preexisting diabetes (35% vs 23%, P < .001) or hypertension (97% vs 94%, P = .029). Black patients had poorer treatment of CVD risk factors, with lower rates of control of diabetes (35% vs 51%, P < .05) and dyslipidemia (37% vs 42%, P < .05). Black renal transplant recipients who had preexisting CVD had reduced graft survival rates compared to white patients (10-year rate 50% vs 60%, P = .033), but similar rates of graft survival were found in those without CVD (10-year rate 70% vs 71% in white patients, P = .483). CVD is common in transplant recipients, with black patients having higher rates and poorer control of diabetes and dyslipidemia.